The effect of voltage on polypropylene microplastics removal by electrocoagulation process using Fe electrode / Norfaezatul Alysa Othman ... [et al.] - Othman, Norfaezatul Alysa; Isa, Norain; Amri, Nurulhuda; Abdul Wahab, Nor Aimi; Bashirom, Nurulhuda (Universiti Teknologi MARA Cawangan Pulau Pinang, 2024)
This study investigates the effect of voltage on the removal of polypropylene microplastics (PPMPs) from artificial wastewater via an electrocoagulation (EC) process using iron (Fe) electrodes. The effect of the voltage was investigated by conducting multiple continuous flow experiments at three different voltage values (10, 20, and 30 V). The findings demonstrated that the turbidity value increased gradually as theinitial voltage increased, from 6.67 NTU at 10 V to 74.37 NTU at 30 V. In this EC process, in which Fe electrodes are utilized to remove the PPMPs, it is believed that 20 V provides optimal support. Kinetic studies showed that the process followed a first-order kinetic model with a kinetics rate constant (k) of 0.0143 min-1 and a coefficient of determination (R2 ) of 0.9702. The findings demonstrated that voltage is a significant parameter in the EC process employing Fe electrodes to remove PPMPs from wastewater.